Pengaruh Campuran Limbah Baglog Jamur dan Kotoran Kambing sebagai Media Pertumbuhan Terhadap Biomassa Cacing Tanah Lumbricus Rubellus - Chalisty, Vian Dwi; Riyanto, Alief (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Mushroom baglog waste provides essential nutrients for earthworm growth, while goat manure serves as a valuable source of nitrogen for their nutrition. This study aimed to determine the effect of a combination of oyster mushroom baglog waste and goat manure on the biomass production of earthworms (Lumbricus rubellus) and the shrinkage of the cultivation media. The main materials were mushroom baglog waste and goat manure as media, and Lumbricus rubellus as the cultivated species. The growth media, composed of lime, baglog waste, and goat manure, was fermented aerobically for 7 days. Earthworms (20 g per treatment) were added and maintained for 40 days, with media turning performed on day 30.The experiment consisted of 6 treatments with 3 replications: P0 (control, 5 kg baglog), P1 (4.5 kg baglog + 0.5 kg goat manure), P2 (4 kg baglog + 1 kg goat manure), P3 (3.5 kg baglog + 1.5 kg goat manure), P4 (3 kg baglog + 2 kg goat manure), and P5 (2.5 kg baglog + 2.5 kg goat manure). Observed parameters included worm biomass weight and media shrinkage. Data were analyzed using a completely randomized design (CRD) with a one-way pattern, followed by Duncan's test if significant differences occurred. Results showed that P1 produced the highest biomass (37.33 g), while P4 had the lowest (10.00 g). Media shrinkage was highest in P0 (11.83 cm) and lowest in P1 and P5 (9.50 cm). Statistical analysis indicated that media shrinkage differed significantly among treatments (P<0.05), whereas worm biomass did not (P>0.05). It can be concluded that the use of 4.5 kg mushroom baglog waste and 0.5 kg goat manure produces high Lumbricus rubellus biomass without significantly affecting media shrinkage over 40 days